Social Learning and Reputation Management in an Espionage Crisis - Kuoppakangas Päivikki; Hagman Sirkka; Stenvall Jari; Kinder Tony (Springer Nature, 2025)
The purpose of this qualitative case study comprising 18 thematic interviews was to explore social learning and provide an internal focus on the development path of an international company coping in a crisis. EC is an international engineering and design agency that grew from a small business to a medium-sized enterprise during the crisis era. Since it began operations in 2011, there has been a suspicion of industrial espionage, directed at the founders of the company, including the CEO. Managing internal and external reputations in these circumstances is challenging, as the company builds its legitimacy. The data were content analysed and the results of the study concluded that social learning is crucial to surviving crises. The abductive content analysis and findings of this study are threefold. First, it is suggested that social learning enhances organisational coping in the midst of a crisis. Next, to manage business development and organisational reputation during the crisis, it is necessary to use distributed learning, thinking and doing simultaneously. Thus, the core business and the need for ongoing espionage crime detection create potential harm to the company’s external reputation. Nevertheless, EC’s revenue continuously increased and the trust of clients was maintained.